The story of Pocahontas - Doherty, Brian; Kliros, Thea (New York : Dover Publications, 1994)
A fictionalized account of the life of Pocahontas who befriended Captain John Smith and the English settlers of Jamestown.
"In easy-to-read type"--Cover.
Keywords: Pocahontas; Pocahontas; Powhatan women; Indians of North America